(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Street vendors (hawkers) face risk while purchasing the products. They do not have any guarantee for selling the purchased goods. The street hawkers face the problems in relating to buying and selling the products and receiving the amount. In considering these points, it is necessary to conduct the study to know more about the same. In this study, the street vendors are not highly satisfied with their job but they are forced by their tradition and the financial condition of their family. Majority of the street vendors suggested that the government should pay the insurance premium for street vendors. Majority of the street vendors prefer this hawking business for small investment, because they can’t invest a large amount of money in their business. Most of the economically back warded families are doing this work. So the Government should help the street vendors to provide subsidy and also loan facilities with low rate of interest from bank easily.